E-COMMERCE; THE NEW PHENOMENON AND HOW TO BE SUCCED IN MARKETPLACE - Santoso, Rudi; Riyanto, Darwin Yuwono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to measure the factors that influence the satisfaction of Brodo e-commerce web users. The growth of e-commerce is also in line with the rapid use of the internet over the last 10 years. Brodo is one of the local businesses that was founded in 2010 and started to use the website address Bro.do as a means for consumers to choose their products easily. This research is descriptive research with a survey method. The independent variables of this study are usability (X1), information quality (X2), service interaction quality (X3), and the dependent variable is User Satisfaction (Y). The research object is Brodo e-commerce web users as many as 100 respondents. The results of the study show that the usability or usability value of e-commerce web applications has an influence on User Satisfaction. The R2 value of this study was 0.463. Meanwhile the results of the partial t test show that only variable X1 (Usability) influences User Satisfaction with a significance value of 0.000 <  (0.05). While the other variables X2 and X3 have no effect on user satisfaction with a significance value of 0.314 and 0.953 respectively >  (0.05)